An assessment of the impacts of electronic ticketing on inspections and material procurement for highway construction - Subramanya, Karthik; Kermanshachi, Sharareh; Pamidimukkala, Apurva; Loganathan, Karthikeyan (Frontiers in Built Environment, 2023)
Introduction: The benefits of incorporating technological advancements and digitalization into construction firms’ inspections and material supply procurement operations have been well documented. Despite this and the availability of the technology, however, there is a pervasive lack of understanding in the industry about the appropriate application(s) and benefits for highway construction. This study aims to 1) assess the merits of e-Ticketing technology based on the benefits it provides to the construction industry, and 2) determine the amount of time that it can save inspectors. Method: A structured survey questionnaire was designed and distributed to a variety of state DOTs to ascertain how they view the benefits of technology, and the advantages cited were ranked according to their importance. Results and Discussion: The time savings that could be realized by incorporating technology into their operations were estimated by comparing the number of personnel required for inspections before and after implementing e-Ticketing and revealed that 24% of the workforce could be eliminated or reassigned. This study contributes to the existing body of knowledge by providing information about how utilizing technology can help state departments of transportation improve the productivity of their workforce, increase safety and morale, minimize schedule delays, mitigate the prevailing shortage of inspection staff, and prepare for the next pandemic or similar event.